Pseudomonas osteomyelitis of the proximal humerus after arthroscopic rotator cuff repair - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2014)
A 59-year-old male patient was operated arthroscopically due to a rotator cuff tear. An early postoperative Pseudomonas aeruginosa infection was treated with early arthroscopic debridement and antibiotic therapy. The patient was lost to follow-up and presented to our clinic with Pseudomonas aeruginosa osteomyelitis after two years. Debridement was again performed and antibiotic-impregnated cement beads were filled into the cavity and taken out 6 weeks postoperatively. No findings of infection were observed at the patient's 2nd year follow-up. To our knowledge, this is the first case of Pseudomonas aeruginosa osteomyelitis of the shoulder after arthroscopic rotator cuff repair.
Keywords: Infection; osteomyelitis; shoulder arthroscopy; BACTERIAL ADHERENCE; SEPTIC ARTHRITIS; SHOULDER; COMPLICATIONS; MANAGEMENT; INFECTION